2020
DOI: 10.18632/oncotarget.27784
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of TRC102 (methoxyamine HCl) in combination with temozolomide in patients with relapsed solid tumors and lymphomas

Abstract: Background: TRC102 inhibits base excision repair by binding abasic sites and preventing AP endonuclease processing; it potentiates the activity of alkylating agents, including temozolomide, in murine models. In published xenograft studies, TRC102 enhanced the antitumor effect of temozolomide regardless of cell line genetic characteristics, e.g., O6-methylguanine DNA methyltransferase (MGMT), mismatch repair (MMR), or p53 status. Materials and Methods: We conducted a phase 1 trial of TRC102 with temo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Alkylating agents and platinum-based compounds used to treat a wide range of solid tumors directly attacking the DNA bases forming covalent DNA adducts that interfere with the progression of DNA polymerases. Expression of O-6-methylguanine-DNA methyltransferase (MGMT) is a commonly used biomarker for the alkylating agent temozolomide in glioma and glioblastoma patients [ 25 ], and temozolomide has recently shown to be effective in combination with the base excision repair inhibitor TRC102 (methoxamine) in patients with relapsed solid tumors and lymphomas [ 53 ] ( Table 1 ). The sensitivity of platinum compounds including cisplatin and carboplatin is increased in triple-negative breast and serous ovarian cancers with overexpression of the Bloom (BLM) helicase [ 54 ].…”
Section: Dna Replication Replication Stress (Repstress) and Maintenance Of Genome Stabilitymentioning
confidence: 99%
“…Alkylating agents and platinum-based compounds used to treat a wide range of solid tumors directly attacking the DNA bases forming covalent DNA adducts that interfere with the progression of DNA polymerases. Expression of O-6-methylguanine-DNA methyltransferase (MGMT) is a commonly used biomarker for the alkylating agent temozolomide in glioma and glioblastoma patients [ 25 ], and temozolomide has recently shown to be effective in combination with the base excision repair inhibitor TRC102 (methoxamine) in patients with relapsed solid tumors and lymphomas [ 53 ] ( Table 1 ). The sensitivity of platinum compounds including cisplatin and carboplatin is increased in triple-negative breast and serous ovarian cancers with overexpression of the Bloom (BLM) helicase [ 54 ].…”
Section: Dna Replication Replication Stress (Repstress) and Maintenance Of Genome Stabilitymentioning
confidence: 99%
“…Another phase I clinical trial (ClinicalTrials.gov Identifier: NCT01658319) focusing on advanced hematologic malignancies showed that, among 20 patients diagnosed with advanced hematologic malignancies excluding acute myeloid leukemia, and administered with methoxyamine in combination with fludarabine, four patients achieved a partial remission, and eight achieved SD 53 . In patients with relapsed solid tumors and lymphomas, TRC102 with temozolomide showed active results, with 4 of 51 patients experiencing a partial response (PR) and 13 having a best response of SD 55 …”
Section: Targeting Ssb and Dsb Repairmentioning
confidence: 99%
“…53 In patients with relapsed solid tumors and lymphomas, TRC102 with temozolomide showed active results, with 4 of 51 patients experiencing a partial response (PR) and 13 having a best response of SD. 55 APE1 activity is also associated with response to radiotherapy. Bobola et al 56 demonstrated that APE1 activity is predictive of outcome following radiotherapy in pediatric ependymoma.…”
Section: Targeting Ape1 In Cancer Treatmentmentioning
confidence: 99%
“…20,21 Several alkoxyamines work with alkylating agents to efficiently kill cells and exhibit encouraging outcomes in Phase I trials as combination chemotherapy agents. 20,22,23 However, no attention has been paid to reducing the side effects on normal cells from unselective AP capture, challenging their future development. 22 The selective release of alkoxyamines by an abundant biomolecule in cancer cells offers a solution for this challenge.…”
mentioning
confidence: 99%
“…20,22,23 However, no attention has been paid to reducing the side effects on normal cells from unselective AP capture, challenging their future development. 22 The selective release of alkoxyamines by an abundant biomolecule in cancer cells offers a solution for this challenge. We describe the use of glutathione (GSH) for this purpose.…”
mentioning
confidence: 99%